1995
DOI: 10.1007/bf02065408
|View full text |Cite
|
Sign up to set email alerts
|

Products of neutrophil metabolism increase ammonia-induced gastric mucosal damage

Abstract: Recent studies have indicated that ammonia is involved in the pathophysiology of Helicobacter pylori-associated gastric mucosal damage. Helicobacter pylori-associated chronic active gastritis is characterized by an invasion of neutrophils. We investigated the interrelationship among hypochlorous acid (oxidant produced by neutrophil), ammonia (product of Helicobacter pylori urease), and monochloramine (product of ammonia and hypochlorous acid) in the development of gastric mucosal damage in rats. Gastric mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…1, 4) Suzuki et al [65] and Murakami et al [66] have reported that H. pylori increases the production of inflammatory cytokines such as IL-1b, IL-2, IL-6, IL-8, and tumor necrosis factor alpha (TNF-a), and that toxic metabolites and lysosomal enzymes released from neutrophils are also responsible for gastric mucosal injury, while Takashima et al [67] reported that decreased acid secretion was accompanied by an elevation of IL-1b messenger RNA levels in the H. pylori-infected gastric mucosa. Esplugues et al [68] and Kondo et al [69] reported that the acidinhibitory effect of IL-1b appears to involve nitric oxide synthesis and may be mediated by the inhibition of gastric histamine mobilization.…”
Section: Endogenous Factorsmentioning
confidence: 96%
“…1, 4) Suzuki et al [65] and Murakami et al [66] have reported that H. pylori increases the production of inflammatory cytokines such as IL-1b, IL-2, IL-6, IL-8, and tumor necrosis factor alpha (TNF-a), and that toxic metabolites and lysosomal enzymes released from neutrophils are also responsible for gastric mucosal injury, while Takashima et al [67] reported that decreased acid secretion was accompanied by an elevation of IL-1b messenger RNA levels in the H. pylori-infected gastric mucosa. Esplugues et al [68] and Kondo et al [69] reported that the acidinhibitory effect of IL-1b appears to involve nitric oxide synthesis and may be mediated by the inhibition of gastric histamine mobilization.…”
Section: Endogenous Factorsmentioning
confidence: 96%
“…The resultant HClO, in turn, interacts with ammonia to generate monochloramine (NH 2 Cl), a high toxic substance on gastric mucosa (2,3). Several studies have reported that either exogenous or endogenous NH 2 Cl at much lower concentrations than ammonia produces gastric mucosal lesions in rats (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Thus, it is possible that NH 4 OH, even at low concentrations, produces NH 2 Cl by interaction with HClO in the ischaemic stomach, resulting in damage to the gastric mucosa. Indeed, Murakami et al 9 have previously reported that the gastric irritable effect of low concentrations of NH 4 OH under ischaemia is totally abolished by antineutrophil serum. Moreover, we observed that exogenously administered NH 2 Cl, a mixture of NH 4 OH and NaHClO, which at low concentrations does not produce any damage to the mucosa, caused severe haemorrhagic lesions in the gastric mucosa of unanaesthetized rats.…”
Section: Discussionmentioning
confidence: 97%
“…7,8 Indeed, it has been demonstrated that NH 2 Cl plays a role in the pathogenesis of NH 4 OHinduced gastric lesions in rats. 9,10 We have also reported that both endogenous and exogenous NH 2 Cl damage the gastric mucosa at much lower concentrations than NH 4 OH. 11,12 In addition, we have recently SUMMARY Background: It is well known that neutrophil-derived hypochlorous acid interacts with ammonia (NH 4 OH) to generate monochloramine (NH 2 Cl) and that NH 2 Cl irritates the gastric mucosa and impairs ulcer healing.…”
Section: Introductionmentioning
confidence: 93%